The Construction of Religious Meaning Through Cultural Events - Nur Hamidah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
This study explores the intersection of religious and cultural festivals, with a focus on their role as tourism commodities, particularly in the case of the Suroan and Larung Saji festivals in Malang Regency, Indonesia. It examines how religious meaning is embedded within these cultural festivals and how they contribute to the preservation of local traditions while promoting religious tourism. The research highlights the strong connection between religious beliefs and cultural practices, where these festivals serve not only as a spiritual expression but also as a significant driver of local economies through religious tourism. The study finds that the commercialization of these festivals has led to the creation of religious tourism destinations, attracting both local and international visitors. The research further identifies the role of cultural festivals in maintaining social identity, as they embody historical values and contribute to cultural preservation. Motivations for attending these festivals are largely driven by religious beliefs and cultural interest, with religious tourism playing a crucial role in sustaining these practices. Moreover, the research suggests that the development of tourism infrastructure and destination branding is vital for enhancing the economic and cultural impact of these festivals. The findings emphasize the importance of balancing tradition and commercialization, ensuring that the cultural and religious significance of the festivals is preserved while supporting the growth of the local tourism industry.